Climate Change Adaptation in Sustainable Agriculture: Implications for Food Security and Sustainability - Dewi Susanti; Ruwaida Ruwaida (CV Projurnal Mitra Publikasi, 2025)
Climate change poses significant pressures on the sustainability of global agricultural systems and food security stability. This study aims to analyze the development of global literature on climate change adaptation in the agricultural sector and identify conceptual gaps and future research directions. The study employs a Systematic Literature Review (SLR) approach combined with bibliometric analysis of reputable international publications. A total of 39 articles were selected for final analysis. The results indicate that agricultural adaptation research has grown rapidly over the past two decades, with a primary focus on Climate-Smart Agriculture (CSA), ecosystem-based resource management, production system diversification, and the integration of digital technologies such as precision agriculture and artificial intelligence. However, the literature remains fragmented and technically oriented, with limited integration between technological innovation, farmers’ adaptive capacity, institutional governance, and the dimensions of food security and social equity. This study proposes an integrative conceptual framework that links technological innovation, ecosystem sustainability, socioeconomic capacity, and public policy in strengthening the resilience of the global food system. These findings provide theoretical contributions and policy implications for accelerating sustainable agricultural transformation amid the dynamics of climate change.